Pots and People from East to West: a Rare Early Islamic Glazed Lidded Bowl from a Monastic Site near Jericho, and Its Cultural and Historical Context - Taxel, Itamar (Archäologischer Anzeiger, 2017)
This article discusses a glazed lidded bowl that was found in the 1930s during the excavation of an Early Islamic Nestorian/East Syrian monastic site near Jericho. The vessel is unique to the Palestinian/Levantine ceramic repertoire, but – as an apparently southern Iraqi product – has identical equivalents at sites located from southern Iran to eastern Arabia. Not only can this lidded bowl be considered one of the earliest glazed vessels ever published from Early Islamic Palestine, but it also represents a rare example of a direct link between people and objects belonging to the same cultural world, both of which are archaeologically attested far from their place of origin. Palestine • Jericho • Early Islamic epoch • alkaline glazed pottery • Nestorian/East Syriac Christianity